Etos Membaca Mahasiswa Jurusan Gizi FKM UIN Sumatera Utara - Harmita Siringo-ringo; Irwansyah Alfaqih; Miranda Situmeang (CV. ULIL ALBAB CORP, 2024)
The purpose of this research is to find out the reading ethos of students in the Department of Nutrition FKM UIN North Sumatra. Using a questionnaire to gather information from a sample of students in the Gorontalo State University information engineering department, the research used descriptive statistics for data analysis. Reading is a valuable skill that offers many benefits, including broadening one's understanding of the world, improving critical thinking and problem-solving abilities, and encouraging personal growth and development. There are several reasons why reading is important, and this study aims to explore these reasons. The research's conclusions are as follows: 1) Students majoring in nutrition still have a relatively low interest in reading books; this is probably because they become bored easily. 2) Students understand the value of reading books despite the findings showing a low interest in reading. 3) Students believe that reading may enhance their capacity for critical thought, that reading can alter their perspective on a subject, that reading can facilitate their academic progress, and that reading can have long-term advantages.